Reducing Sodium Consumption in Mexico: A Strategy to Decrease the Morbidity and Mortality of Cardiovascular Diseases - Campos-Nonato, Ismael; Vargas Meza, Jorge; Nieto, Claudia; Ariza, Ana Carolina; Barquera, Simón (Frontiers in Public Health, 2022)
Hypertension (HTN) and cardiovascular diseases (CVD) are important public health problems in Mexico. High sodium intake is linked to high blood pressure and increased risk of developing CVD. International organizations suggest consuming less than 2 g of sodium/day; however, the Mexican population consumes amounts above what is recommended: 3.1 g/day. Although efforts have been made to mitigate this problem, interventions are needed to improve cardiovascular health. This policy brief offers a short review of the current sodium consumption situation in Mexico and the importance of why decision makers should consider actions to reduce consumption. Recommendations to reduce sodium/salt intake include: Promote the use warning labels, reformulation of ultra-processed-foods, reduce the use of table salt, and monitor sodium intake.